SUFISTICS OF THE SOCIAL TRANSFORMATION ERA (Deconstruction of Jalaluddin Rakhmat's Thought) - Herianti, Herianti (Universitas Islam Negeri Alauddin Makassar, 2018)
The purpose of this study is to describe: characteristics of the era of social transformation in general and the deconstruction of Sufistic Jalaluddin Rachmat’s thought in the social transformation era, so that misunderstanding of Sufism can be overcome by displaying Sufism's simple teachings without reducing the meaning of its substance, so that it is easily practiced by all groups. The approach used is a philosophical and sociological approach. This type of research is classified as library research with processing methods and data analysis which is qualitative. Data is collected by quoting, adapting and analyzing the literature that is representative and has relevance to the problem discussed, then reviews and concludes it. After holding a discussion on the thinking of Sufistic Jalaluddin Rachmat by emphasizing Sufistic thinking in the era of social transformation, as a result Jalaluddin Rachmat divided Sufism into three mahzab, i.e. morality mahzab, ma'rifat mahzab and essence mahzab. Implication of this research is to minimize the occurrence of various forms of deviation both individual and social. In addition, this research also calls on the readers or the public to continue to preserve the teachings of Sufism by deconstructing the teachings of other Sufism so that it is always fresh and can be transformed in accordance with the rate of development of the times.